Enhancing academic self-concept and historical literacy in Islamic studies through collaborative learning: a study on prospective Islamic Education teachers in Indonesia - Agus Fakhruddin; Saepul Anwar; Mohammad Rindu Fajar Islamy (Cogent Education)
Islamic historical literacy is essential for Islamic Religious Education (PAI) teachers, as it involves understanding the context of Islamic teachings. For prospective PAI teachers, this literacy is fostered through courses in Islamic civilization history, with development influenced by their academic self-concept. This research’s first-year study aimed to explore the academic self-concept and Islamic historical literacy levels of prospective PAI teachers, without assessing the relationship between these two variables. A quantitative survey approach was used, involving students from the 2021 to 2023 cohorts at a state university in Bandung who had enrolled in the History of Islamic Civilization course. Data were collected through a Likert-scale questionnaire and analyzed descriptively. Results showed that nearly all respondents possessed a good academic self-concept, although a small number required improvement, particularly in the cognitive aspect. Similarly, 91% of respondents demonstrated a good level of Islamic historical literacy, with 31% achieving very high literacy. These findings suggest that Islamic civilization history courses positively impact both academic self-concept and Islamic historical literacy. In the second year, experimental research will be conducted to assess the effectiveness of collaborative learning within this course in further enhancing these attributes among prospective PAI teachers.